2014
DOI: 10.4236/ojped.2014.41012
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Novel Low Cost Intervention to Reduce Prenatal Alcohol Exposure in the Congo

Abstract: Objective: Determine the effectiveness of an intervention to reduce prenatal alcohol exposure in the Congo. Methods: We utilized a screening tool validated in the Congo to identify women who were drinking during pregnancy. The intervention was implemented by prenatal care providers comparing 162 women receiving the intervention with 58 (controls) who did not. The study endpoints were proportion of women who quit drinking, drinking days per week, drinks per drinking day, most drinks on any day, and number of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Williams et al [ 54 ] demonstrated a low-cost community intervention strategy for reducing prenatal alcohol exposure in the Congo. Such interventions may also successfully control prenatal alcohol and tobacco in the Nigerian setting.…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al [ 54 ] demonstrated a low-cost community intervention strategy for reducing prenatal alcohol exposure in the Congo. Such interventions may also successfully control prenatal alcohol and tobacco in the Nigerian setting.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that understanding the effects of alcohol on the baby from breastfeeding may be more intuitive because the baby is visibly ingesting fluid, whereas nutrient transfer via the placenta during pregnancy is unobservable. Despite key structural determinants of alcohol use, brief communication of the risks of alcohol can be an effective, low-cost and easy-to-administer intervention, and has been utilised successfully in urban Congolese settings [ 41 ]. Our findings suggests that such interventions may be beneficial for Mbendjele people, though their effectiveness among hunter-gatherer societies remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…The PCAP model has been adopted in numerous locations in North America (Thanh et al, 2015) and is one example of an intervention that addresses the context of alcohol use during pregnancy for the targeted sub-population in a supportive manner (Pei et al, 2019). Another example is a very low cost, in-office pictorial intervention program for alcohol use in pregnancy that was developed and tested in the same communities in the Congo, which continues to be studied as a model for sub-Saharan countries (Williams et al, 2014). Furthermore, participation in programs such as the WIC in the USA can increase utilization of prenatal care among women at risk of alcohol-exposed pregnancies (Richards et al, 2010), which indirectly facilitates the detection and prevention of PAE.…”
Section: Improving Detection and Prevention Of Paementioning
confidence: 99%